Evaluation of intratracheal salbutamol effects in addition to surfactant in the clinical course of premature neonates with respiratory distress syndrome - Razieh Moazami Goudarzi; Zohreh Badiee; Alireza Sadeghnia; Behzad Barekatain (Journal of Research in Medical Sciences, 2023)
Background: In addition to surfactant deficiency, secretion of fluid from blood to the lungs and increase in the fluid content of the lung play significant roles in the pathogenesis of respiratory distress syndrome (RDS). Thus, we aimed to evaluate the effect of salbutamol (a beta-agonist) on fluid clearance from the lungs in neonates with RDS. Materials and Methods: This randomized controlled clinical trial included 82 neonates with RDS admitted to the neonatal intensive care units of Alzahra and Shahid Beheshti Hospitals of Isfahan University of Medical Science from 2017 to 2018. Patients were recruited through convenience sampling. They were randomized into two groups, using simple randomization: 42 were only treated with intra-tracheal surfactant (control group) and 40 with intra-tracheal surfactant plus salbutamol (intervention group). The two groups were compared regarding intubation surfactant administration and extubation (INSURE) failure, duration of nasal continuous positive airway pressure, intubation, oxygen therapy, morbidity, and mortality. Results: INSURE failure leading to mechanical ventilation occurred in 3 neonates in the control group and 2 in the intervention group (P = 0.680). Mean hospital length of stay did not differ significantly between groups (P = 0.230). Comparison of controls with the intervention group regarding complications and the incidence of morbidities revealed no statistically significant difference (P > 0.05). Conclusion: Findings of this study were not in favor of the routine use of salbutamol in neonates with RDS as it did not improve the course of the disease among newborns.